Estradiol reduction through aromatase inhibition impairs cocaine seeking in male rats - Alvarado-Torres, John K.; Morales-Silva, Roberto; Sanabria Ponce de Leon, Alexia; Rodriguez-Torres, Genesis; Perez-Torres, Joshua; Perez-Perez, Yobet; Mueller, Devin; Sepulveda-Orengo, Marian T. (Frontiers in Behavioral Neuroscience, 2024)
Clinical and preclinical research on cocaine use disorder (CUD) has shown that sex differences in drug seeking are influenced by hormonal fluctuations. Estradiol, a sex steroid hormone, has been linked to female drug effects, vulnerability to use/abuse, and psychosocial factors. Preclinical studies showed that estradiol in females facilitates the extinction of cocaine-seeking behavior indicating a possible role in regulating extinction learning. Similar to females, males’ brains contain the aromatase enzyme which coverts testosterone to estradiol. However, it is unclear whether estradiol plays a role in male extinction learning as it does in females. Furthermore, how endogenously aromatized estradiol affects drug addiction in males is unknown. Therefore, this study investigated whether endogenous estradiol regulates cocaine seeking in male rats. We hypothesized that decreased aromatase enzyme activity, resulting in decreased estradiol synthesis in male brains, will impair extinction learning leading to increased cocaine-seeking behavior. This hypothesis was tested using cocaine-conditioned place preference (CPP), and short access self-administration (SA), followed by extinction and reinstatement. Before each extinction session for CPP or SA, male rats received an injection of either 1 (low dose) or 2.5mg/kg (high dose) of the aromatase inhibitor Fadrozole (FAD), or vehicle. FAD groups showed dose-dependent effects on cocaine-seeking behavior compared to the vehicle group during CPP extinction. Specifically, low dose FAD facilitated extinction of cocaine CPP, whereas high dose FAD impaired it. In contrast, neither dose of FAD had any effects on the extinction of cocaine SA. Interestingly, only the low dose FAD group had decreased active lever pressing during cue- and cocaine primed-reinstatement compared to the vehicle group. Neither dose of FAD had an effect on sucrose extinction or reinstatement of sucrose seeking. These results from CPP experiments suggest that estradiol may impact extinction learning, as a low dose of FAD may strengthen the formation of cocaine extinction memory. Additionally, in male rats undergoing cocaine SA, the same low dose of aromatase inhibitor effectively reduced reinstatement of cocaine-seeking behavior. Thus, estradiol impacts cocaine seeking and extinction in both males and females, and it may also influence the development of sex-specific treatment strategies for CUD.